(untitled) (Journal of actual problems of jurisprudence, 2019)
In the scientific article covers legal issues to ensure food security in the CIS. The study found deficiencies in the law of food security in the CIS, we suggested ways to improve these laws. Analyzing the program of agriculture in the agrarian policy of the CIS,we have found ways to address the agricultural sector. Keywords: food security, agricultural policy, agro-industrial complex, integration.